Effectiveness Of Non-Pharmacological Coping Strategies For Labor Pain Management In Women: A Systematic Review - Rejeki, Sri; Ariska, Siti Linda; Khayati, Nikmatul; Dhamanik, Reina (Chakra Brahmanda Lentera Institute, 2026)
Background: Labor is a natural physiological process often accompanied by severe pain, which varies among mothers. Uncontrolled pain may increase catecholamine levels, inhibit uterine contractions, prolong labor, and affect fetal well-being. Non-pharmacological approaches offer an important alternative for pain management. This review aims to synthesize evidence on the effectiveness of non-pharmacological coping strategies in reducing labor pain intensity. Methods: This study is a Systematic Literature Review referring to the PRISMA 2020 guidelines. Article searches were conducted in Google Scholar, Semantic Scholar, PubMed, ScienceDirect, and ProQuest databases for the 2021–2025 period using the keywords “coping,” “managing,” and “labor pain.” Inclusion criteria included RCTs, quasi-experimental studies, observational studies, and systematic reviews in English or Indonesian discussing non-pharmacological coping strategies. A total of 11 articles met the criteria and were analysed using the PICOT framework. Results: Identification through database searching (n =150), articles screened based on title and abstract (n= 110). Remaining relevant articles: 70, Full-text articles reviewed (n =30), and Articles meeting inclusion criteria and synthesized in the final review (n = 11). The synthesis shows that various non-pharmacological coping strategies, such as breathing exercises, music therapy, back massage, use of a birth ball, aromatherapy, acupressure, and emotional support, are effective in reducing pain intensity and anxiety during labor. Conclusion: Non-pharmacological coping strategies are proven effective, safe, and empowering for mothers. Implications for practice may consist of Multimodal coping strategies that improve maternal outcomes, Non-pharmacological methods that reduce reliance on analgesics, and Interventions feasible in low-resource settings